Dr. Eugene Black and six Fletcher School students - Unknown (Tufts Archival Research Center, 2007)
8x10. This date is approximate. From left to right: Manaspas Xuto, Bette Bao, Hisami Mano, Dr. Eugene Black, Suchati Chutasmit, unidentified and Dong Hoon Choi.